Resource-focused Research for Multilingual Competence in Scientific Writing - Brinkschulte, Melanie; Stoian, Monica-Elena; Borges, Ellen (Journal of Academic Writing, 2015)
This research aims to analyse the situation of the multiliteracy of natural sciences students in their academic writing in the German university context and to identify students' awareness and applications of their multilingual writing competence as well as how they make use or not of it in their academic writing process. English has the status of lingua franca in this context and German is used in informal settings. Minutes, reports, reviews, Bachelor or Master theses have to be written either in English or German, depending on the study programme. As Canagarajah (2013) has pointed out, multilingual scholarship offers huge resources in terms of diversity of thinking because language carries with it a system of knowledge and thinking from which both their representatives and the writing scientific community can benefit. The empirical, qualitative study of this paper is based on interviews conducted with participants of the course 'Akademisches Schreiben fur Naturwissenschaftler/innen' (Academic Writing for Natural Sciences Students) offered by the International Writing Centre at Göttingen University. The qualitative content analysis is based on portfolio activities and interviews conducted with students. This paper presents the first results of our data analysis.